Reduction of the Accompanying Noise when Hidding in an Audio File - Radwan Al-Jawadi; Adel Issa (Al-Rafidain Journal of Computer Sciences and Mathematics)
The stereography which used to hide certain information using a host file is a science and an art. Such practice is usually done to keep away any thought in the presence of a hidden message in the host. Hiding is often done using sound, image or video files. The problem is that such hiding may cause some detectable changes in the host file .This study focuses on hiding in WAVE type sound file. Sound files are either one-byte sample or two- byte sample .The hiding idea involves the replacement of the original data by another data from a text file. The first four bits from each byte are used in wave file as a hiding domain. Accordingly, a hiding system was designed for the reduction of the accompanying noise. In this research, it was depended on the human herring for group of people to calculate the reduction in the noise of the host file .It was also shown that hiding in 8-bit sample (1 byte) results in a clearly detectable noise. This jumping 10 bytes in each replacement process led to eliminate the noise .It was also concluded, that when using first and second bit from each byte the noise was completely eliminated by jumping 30 byte. On the other hand, hiding in 16-bit sample (2byte) has led to complete disappearance of the noise when jumping 10 byte at each data replacement process.